Hematological and biochemical parameters in elite soccer players during a competitive half season - Andelkovic, M.; Baralic, I.; Dordevic, B.; Stevuljevic, J. K.; Radivojevic, N.; Dikic, N.; Skodric, N.; Radojevic, S.; Stojkovic, M. (Journal of Medical Biochemistry, 2015)
Background: The purpose of the present study was to report and discuss the hematological and biochemical behavior of elite soccer players, in order to get more insight in the physiological characteristics of these sportsmen and to provide trainers and sports doctors with useful indicators.